Association of Lithuania and European Union - Maniokas, Klaudijus (Politologija, 2025)
It is argued in this article that the signature of the Europe (Association) Agreement between Lithuania and the EU has formally articulated partial change in Lithuania's and its northern neighbours' geopolitical status. The author claims that the state of association with the EU and forthcoming membership in this economic organisation is one of the core strategic destinations of Lithuania's foreign policy, which, as the author emphasises, are vitalised by Lithuania's national interests.In the first part of this article, the author tries to trace and elucidate the main currents of this process of integration as well as factors affecting it and to evaluate the upbrought with respect to national interests of Lithuania. In this primary part of the work, a review on Lithuania-EU relations is propounded, three chronological stages of the development are researched, main complexities and issues are exposed. The author emphasises that there are two types of rapprochement provided by the EU member states in framing their ties with the former USSR satellites: one, devoted to Central European Countries, and the other - to former USSR. It is challenged that Lithuania stands somewhere in its mid-position and proposes four factors why Lithuania is expected to gradually gravitate towards the first-type relations, which stipulate the transformation of the status of the Baltic States.In the second part, the content and character of the Europe Agreement are analysed and evaluated on the basis of the same Lithuania's national interests. The third part is devoted to the major problem encountered during the process of negotiations on the Europe Agreement, namely the acquisition of land by foreigners. This question has particular significance since it was the very first time when Lithuania's politicians and population in general confronted reality associated with the EU. The author clarifies different aspects of the free trade agreement, asserting the many-facedness of European politics.Hence, in the last part of the article, the author tries to evaluate the perspectives of Lithuania-EU relations. Important external factors of NATO expansion and arising conflictuality of NATO-Russia policy towards the Baltic region are researched as having an indispensable and inevitable role in the shaping of the terms of gradual integration to the EU as well as the whole nature of rapprochement itself. The author sanctions an important role to the United States. This study also propounds the internal factor, i.e., the readiness of Lithuania itself for the entry into the European Union. Maniokas manages to illustrate his arguments with highly accurate facts from the events in the global political arena.
Keywords: -